DEMİR YÜKLEMESİNİN DOKU DEMİR DÜZEYLERİNE ETKİLERİ - SEYMEN, H. Oktay; ÖZÇELİK, Derviş; GÜLYAŞAR, Tevfik; MENGİ, Murat; SEYMEN, Pınar; YİĞİT, Günnur (Cerrahpaşa Medical Journal, 2019)
Background and Design.- The harmful effects of acute and chronic iron loading are well documented. Increased lipid peroxidation is an important expression of both chronic and acute iron toxicity. Our aim was to study the effect of iron owr1oading on the different tissue lewls of iron. Results.- 14 adult male Wistar albino rats weighing 200-250g were used. The animals were dhlided into 2 weight-matched groups. Group 1: Control group (n=7) and Group 2: Iron owr1oading group (n=7). The rats in group 2 receiwd intraperitoneal iron (Ferro Ill hydroxide polymaltose) at a dose of 250 mg/kg/day for 10 days. At the end of the administration period, the rats were anesthetized by ketamine (50 mg/kg). Heparinized blood samples were obtained \Jia aorta abdominalis. The samples of the tissue from liwr, heart, spleen, brain and skeletal muscle were obtained. The plasma and the tissue lewls of iron were measured by atomic absorbtion spectrophotometer. The plasma free iron values for rats recei\Jing iron were significantly (p<0.001) higher. This finding confirmed the establishment of the iron owr1oading state. The liwr, heart, spleen, and skeletal muscle tissue lewls of iron were significantly higher (p<0.001, p<0.01, p<0.05, p<0.05 respectiwly) than those of control rats. There was no significant difference between two groups brain tissue lewls of iron {p>0.05). Conclusion.- Our results show that the liwr cells haw the most capability of iron storage.